(untitled) (Geo-Eco-Marina, 2013)
The landslides along the Northern Black Sea coast, between the Varna City and Kavarna town, may be divided in the following six regions, according to their geological structure, geomorphological and engineering geological settings: I – Varna city – Golden Sands resort; II – Golden Sands resort – Kranevo village; III – Batova River valley; IV – Batova River – Balchik town; V – Balchik town – Topola village; VI – Topola Dere –Kavarna town and northward of it. The results of the new engineering geological investigations, made mainly in regions II, III and V, are discussed in the paper. They include geological and engineering geological mapping, photo surveying of the terrain by a helicopter, geodetic surveys, re-interpretation of data from old drilling, considerable number of new boreholes and resistivity survey (RS), slope stability analyses, and engineering geological zoning. The main result of these investigations is the elaboration of a new geological model with tiered landslide steps, where the sliding surfaces are not connected between them. In the previous studies, the presence of an unified rupture surface from the plateau till the sea cost has been accepted. The separate landslides, their lithology and stratigraphy, geomorphology and engineering geology are also described. Several marine terraces are established and dated. Based on this, the age of landslides is determined. The major factors for the origin of the studied landslides are: the eustatic fluctuations of the sea during the Pliocene and Pleistocene, the constant uplifting of the dry land, the relatively high slope inclination, the high seismicity (IX degree, according to the MSK scale), and the anthropogenic activity at present. The lithological-stratigraphic structure of the Sarmatian sediments is an important prerequisite for the slope instability.